Evaluating the Performance of Dar Al Salam Investment Bank / Baghdad Using the financial indicators for the years 2005 through 2015 - Osman Amin Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The financial analysis of the budgets and balances of banks is the appropriate framework for conducting the diagnosis on the basis that each difference in the status of the bank will appear through financial indicators, because the figures in the financial statements do not clearly reflect the fact of financial position, so the financial ratios reveal important relationships between The figures appearing in these lists in order to give the bank an early indication of intervention to address a particular problem and to take appropriate corrective measures in the necessary, ie work to address the weaknesses and strengthen the strengths, helping them to achieve the interests of the parties involved in it. A set of financial ratios is applied to the financial statements of Dar al Salaam Investment Bank for the years 2005 through 2015 to find out most aspects of its performance during these years. The research found that the financial indicators applied to the bank indicate that the bank maintains high liquidity, which provides protection to depositors, which raises their confidence in the bank, but in contrast, maintaining high liquidity by the bank to low profitability of the bank, which negatively affects the maximization of shareholders' wealth and stock market price Iraq's securities, and here we say that the performance of the bank is not good but we say that it is compatible with the current stage, which is characterized by instability, which necessitates the bank to maintain high liquidity funny part of the profit and low price of its share in order to continue and reach a better stage enabling it Investment at the expense of liquidity increases the profitability of the bank and the share price. The research hypothesis has been proved that there is an inverse relationship between liquidity, profitability and banking performance, and a positive relationship between profitability and banking performance.